The Effectiveness of Utilizing Digital Media in Enhancing Career Guidance Services Provided by School Counselors at Various Levels of Education - Nur Maulinda Yanas; Ramli Ely; Nurul Padillah Pausia; Nasirah Dian Ayunur; A. Aisyah Tun Nafsia; Novi Febianti (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the effectiveness of digital media in enhancing student engagement and career readiness in career guidance and counseling services. This research employs a qualitative method based on a literature review. The literature used is derived from scientific journals and relevant articles discussing the utilization of digital technology in career guidance services. The data collection process involved a systematic search of Google Scholar using keywords aligned with the study's focus. The data were analyzed by identifying, classifying, and synthesizing the main themes that emerged from the systematically reviewed literature. The results indicate that the use of digital media, such as instructional videos, online service platforms, and game-based learning media, consistently increases student engagement, motivation, and active participation in career guidance services. The use of digital media facilitates easier access to information, offers flexibility in time and place, and creates a more interactive and engaging service environment. These conditions enable students to obtain broader, more in-depth career information, thereby supporting the tailored improvement of career readiness for each student's needs and characteristics. The use of digital media by school counselors can serve as an innovative and adaptive strategy to improve the quality of career guidance services in schools. The appropriate selection and use of digital media are expected to help students better prepare to meet the evolving dynamics and demands of the labor market.